Comparation Of Post-Divorce Marriage Agreements Compilation Perspective Of Islamic Law And Maqashid Sharia - Nuriana, Kartika Ayu; Huda, Masrur; Aliyah, Nelud Darajaatul (VISA: Journal of Vision and Ideas, 2025)
Humans as living beings were created by Allah SWT as complementary social beings, living in pairs in the world. As part of paired life, human beings undergo the process of marriage to continue offspring and ensure the continuity of future generations. The purpose of marriage itself is as a form of perfection of human worship in the long run. The marriage formed by a married couple aims to create a lasting and happy family, based on law and religion based on the Almighty God. The application of a marriage agreement agreed upon by a married couple aims to build a harmonious relationship and prevent future conflicts. One form of marital agreement regulated in positive law in Indonesia is regarding taklik talak. A marriage agreement that is often applied is the regulation of joint property in marriage, which is stated in Article 29 of Law Number 1 Year 1974 jo Law Number 16 Year 2019 concerning Marriage. In Islam, the arrangement for making a marriage agreement must follow the provisions stipulated in the Compilation of Islamic Law. The method used in this research is normative research.